Aspek Biomekanika Forensik Pada Trauma Peluru Plastik Airsoft Gun - Sugiharto, Ade Firmansyah; Pattihahuan, Ira Zefanya (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
The biomechanical aspects of trauma caused by airsoft gun plastic pellets depend on the energy generated by the pellet and the tissue resistance. The airsoft gun plastic pellet creates lower energy compare to firearm, thus creating non-lethal effect to human body, but sufficient for creating tissue damage. This energy is determined by the velocity, weight, and diameter of the plastic pellet.. Indonesia allows for a maximum of 2 Joule energy, 8 mm in diameter, and 0,4 gram in maximum weight for airsoft gun plastic pellet. When it hits body surface, this characteristics will create energy of 3,98 J/cm2, and 7 J/cm2 with 6 mm plastic pellet diameter. The most common case of injury due to airsoft gun plastic pellet is eye ball injury. With a resistance of 4.3-4.8 J/cm², trauma from airsoft gun plastic pellets can result in corneal abrasion, hyphema, contusion, and even rupture.. Skin has much higher resistance, which is 23,99 J/cm2. Some injury may still be found, including erythema and 5 mm skin penetration.